Impact of long‐term storage of plasma and cell‐free DNA on measured DNA quantity and fetal fraction. Issue 7 (28th April 2020) - Clausen, Frederik Banch; Barrett, Angela N.; Advani, Henna V.; Choolani, Mahesh; Dziegiel, Morten Hanefeld
Abstract : Background and objective: Optimal sample storage conditions are essential for non‐invasive prenatal testing of cell‐free fetal and total DNA. We investigated the effect of long‐term storage of plasma samples and extracted cfDNA using qPCR. Materials and methods: Fetal and total cfDNA yield and fetal fraction were calculated before and after storage of plasma for 0–6 years at −25°C. Dilution experiments were performed to investigate PCR inhibition. Extraction with or without proteinase K was used to examine protein dissociation. Storage of extracted cfDNA was investigated by testing aliquots immediately, and after 18 months and 3 years of storage at −25°C. Results: We observed a marked increase in the levels of amplifiable fetal and total DNA in plasma stored for 2‐3 years, and fetal fraction was slightly decreased after 3 years of storage. cfDNA detection was independent of proteinase K during DNA extraction in plasma samples stored >2 years, indicating a loss of proteins from DNA over time, which was likely to account for the observed increase in DNA yields. Measured fetal and total DNA quantities, as well as fetal fraction, increased in stored, extracted cfDNA. Conclusion: Fetal and total cell‐free DNA is readily detectable in plasma after long‐term storage at −25°C. However, substantial variation in measured DNA quantities and fetal fraction means caution may be required when using stored plasma and extracted cfDNA for test development or validation purposes.